PENGARUH PENGETAHUAN DAN SIKAP WANITA PUS TERHADAP KEIKUTSERTAAN DALAM PENGGUNAAN MKJP DI DESA SILEBO-LEBO KECAMATAN KUTALIMBARU KABUPATEN DELI SERDANG TAHUN 2016 - NURHAMIDA FITRI (STIKes Mitra Husada Medan, 2018)
National Family Planning Movement is prepared to build optimal human resources, characterized by increasing community participation in meeting the need to be able to build a prosperous family in the context of family planning services. One of the strategies of implementing family planning programs as stated in the 2010-2014 Medium Term Development Plan (RPJM) is the use of long-term contraceptive methods (MKJP), in the use of MKJP that the provision of complete and clear information and counseling will facilitate acceptors to strengthen usage contraception, for quick and precise action taking. With KIE (Communication, Information, Education) was also able to change knowledge of attitude and behavior of someone who initially did not know and did not want to follow KB program then changed into know and eventually become acceptor of KB and even using MKJP (Long Term Contraception Method). Population in reaserch it is a whole mother fertile in Desa Silebo-Lebo Kecamatan Kutalimbaru Kabupaten Deli Serdang which consisted of 63 people and methods the sample collection in this reaserch is by using totol of sampling. The result showed that variable knowledge and attitude in unison give significant impact on variables bound (the participation of this program) with this program is expected to healthed workers at community in Desa Silebo-Lebo to give information and motivation to the mothers so that using contraceptives the modern or natural.